Attachment theory and research in clinical work with adults - Obegi, Joseph H.; Berant, Ety (Guilford Press, 2009)
Written with the practicing psychotherapist in mind, this invaluable book presents cutting-edge knowledge on adult attachment and explores the implications for day-to-day clinical practice. Leading experts illustrate how theory and research in this dynamic area can inform assessment, case formulation, and clinical decision making. The book puts such concepts as the secure base, mentalization, and attachment styles in a new light by focusing on their utility for understanding the therapeutic relationship and processes of change. It offers recommendations for incorporating attachment ideas and tools into specific treatment approaches, with separate chapters on psychoanalytic, interpersonal, cognitive-behavioral, and emotionally focused therapies.